Heuristics and Dynamics of Economic Decision-Making in Pesantren: An Exploratory Qualitative Approach - Rais Abdullah; Abiyajid Bustami; Darihan Mubarak; Norfaizah Othman (INSTITUT AGAMA ISLAM SEBI, 2026)
This study aims to examine the heuristics and dynamics of economic decision-making in Pesantren by integrating perspectives from behavioural economics and Islamic economics. Unlike the assumption of full rationality in neoclassical economics, this study views economic decisions as the result of interactions among cognitive limitations, actors' experiences, institutional structures, and normative values. The study used an exploratory qualitative approach, with in-depth interviews conducted with nine key informants from two Pesantren in East Kalimantan and West Nusa Tenggara. The results of the study show that decision-makers in pesantren generally use heuristics as an adaptive strategy in dealing with uncertainty and information limitations. In the process, cognitive biases such as anchoring, loss aversion, and overconfidence emerge, with varying intensities depending on governance capacity and the level of decision centralisation. The findings also show that Islamic values, particularly trust, prudence, and benevolence, do not negate the existence of heuristics and biases but play an important role in shaping how economic decisions are justified, evaluated, and studied. The differences among Pesantren reflect greater variations in institutional capacity than in value orientation. This research makes an empirical contribution to understanding the economic decision-making process in Pesantren and offers implications for strengthening governance aligned with Islamic principles and behavioural economic insights. Studi ini bertujuan untuk meneliti heuristik dan dinamika pengambilan keputusan ekonomi di pesantren dengan mengintegrasikan perspektif dari ekonomi perilaku dan ekonomi Islam. Berbeda dengan asumsi rasionalitas penuh dalam ekonomi neoklasik, studi ini memandang keputusan ekonomi sebagai hasil interaksi antara keterbatasan kognitif, pengalaman aktor, struktur kelembagaan, dan nilai-nilai normatif. Studi ini menggunakan pendekatan kualitatif eksploratif, dengan wawancara mendalam yang dilakukan dengan sembilan informan kunci dari dua pesantren di Kalimantan Timur dan Nusa Tenggara Barat. Hasil studi menunjukkan bahwa pengambil keputusan di pesantren umumnya menggunakan heuristik sebagai strategi adaptif dalam menghadapi ketidakpastian dan keterbatasan informasi. Dalam prosesnya, bias kognitif seperti anchoring, loss aversion, dan overconfidence muncul, dengan intensitas yang bervariasi tergantung pada kapasitas tata kelola dan tingkat sentralisasi keputusan. Temuan juga menunjukkan bahwa nilai-nilai Islam, khususnya kepercayaan, kehati-hatian, dan kebajikan, tidak meniadakan keberadaan heuristik dan bias tetapi memainkan peran penting dalam membentuk bagaimana keputusan ekonomi dibenarkan, dievaluasi, dan dipelajari. Perbedaan antar pesantren mencerminkan variasi yang lebih besar dalam kapasitas kelembagaan daripada dalam orientasi nilai. Penelitian ini memberikan kontribusi empiris untuk memahami proses pengambilan keputusan ekonomi di pesantren dan menawarkan implikasi untuk memperkuat tata kelola yang selaras dengan prinsip-prinsip Islam dan wawasan ekonomi perilaku.